Cell therapy medicinal product regulatory framework in Europe and its application for MSC-based therapy development - Ancans, Janis (Frontiers in Immunology, 2012)
Advanced therapy medicinal products (ATMPs), including cell therapy products, form a new class of medicines in the European Union. Since ATMPs are at the forefront of scientific innovation in medicine, specific regulatory framework has been developed for these medicines and implemented from 2009. The Committee for Advanced Therapies (CAT) has been established at European Medicines Agency (EMA) for centralized classification, certification and evaluation procedures, and other ATMP related tasks. Guidance documents, initiatives and interaction platforms are available to make the new framework more accessible for small and medium-sized enterprises, academia, hospitals and foundations. Good understanding of centralised and national components of the regulatory system is required to plan product development. It is in the best interests of cell therapy developers to utilise provided resources starting with the preclinical stage. Whilst there have not been mesenchymal stem cell (MSC) based medicine authorisations in the EU, three MSC products have received marketing approval in other regions since 2011. Information provided on regulatory requirements, procedures and initiatives is aimed to facilitate MSC based medicinal product development and authorisation in the EU.